BRAC University new campus development project construction schedule (01.09.2021-30.09.2021) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding BRAC University new campus development project construction schedule from 01.09.2021 to 30.09.2021.